How to design a study to evaluate therapeutic drug monitoring in infectious diseases?. (August 2020) - Märtson, A.-G.; Sturkenboom, M.G.G.; Stojanova, J.; Cattaneo, D.; Hope, W.; Marriott, D.; Patanwala, A.E.; Peloquin, C.A.; Wicha, S.G.; van der Werf, T.S.; Tängdén, T.; Roberts, J.A.; et al.
Abstract: Background: Therapeutic drug monitoring (TDM) is a tool to personalize and optimize dosing by measuring the drug concentration and subsequently adjusting the dose to reach a target concentration or exposure. The evidence to support TDM is however often ranked as expert opinion. Limitations in study design and sample size have hampered definitive conclusions of the potential added value of TDM. Objectives: We aim to give expert opinion and discuss the main points and limitations of available data from antibiotic TDM trials and emphasize key elements for consideration in design of future clinical studies to quantify the benefits of TDM. Sources: The sources were peer-reviewed publications, guidelines and expert opinions from the field of TDM. Content: This review focuses on key aspects of antimicrobial TDM study design: describing the rationale for a TDM study, assessing the exposure of a drug, assessing susceptibility of pathogens and selecting appropriate clinical endpoints. Moreover we provide guidance on appropriate study design. Implications: This is an overview of different aspects relevant for the conduct of a TDM study. We believe that this paper will help researchers and clinicians to design and conduct high-quality TDM studies.